Finite element modeling of low heat conducting building bricks (2012)
Heat conduction through conventional and interlocking building bricks with cavities was studied in this work. Heat transfer analysis was carried out using MATLAB® partial differential equation toolbox. Regular and staggered hole arrangements were studied. Results showed that four staggered holed interlocking bricks were effective in thermal resistance into the bricks and increasing the holes beyond four did not give any thermal resistance advantage. For the conventional bricks staggered holes did not give any thermal resistance advantage but the four-holed bricks were also adjudged to be effective in thermal resistance into the brick surface. Increasing the number of holes beyond four in conventional bricks did give some thermal resistivity advantage but very minimal. Structural strengths of holed bricks were not considered in this study